TINJAUAN TERHADAP TINGKAT KEPATUHAN PELAPORAN PPh PASAL 23 OLEH WAJIB PAJAK TERDAFTAR DAN PENERIMAANNYA PADA KPP PRATAMA JAKARTA PULOGADUNG - Simanungkalit, Johanna Triasih Simanungkalit; Sitorus, Frangky Yosua; L.Tobing, Suzanna Josephine (Fakultas Ekonomi Universitas Kristen Indonesia, 2018)
Currently Tax is one of the main sources of state revenue. It can be seen from the 2015 APBNP posture and the 2017 State Budget of the Republic of Indonesia Therefore, from year to year the government continues to work to optimize state revenue. Income Tax Article 23 is a type of tax, which is a non-oil and gas income tax included in the income tax section, income tax 23 is imposed on dividends, royalties, technical services, other services. One indicator of tax revenue is the level of taxpayer compliance. Which includes the level of tax compliance is compliance in paying taxes and compliance in reporting taxes. Taxpayer compliance is an important factor in realizing tax revenue targets. The higher the level of tax compliance the higher the level of tax revenue. The purpose of this study is to (1) The purpose of this study is to know tingakat compliance reporting Article 23 Income Tax in KPP Pratama Jakarta Pulogadung. (2) The author also can know the realization of taxpayer income tax Article 23, than the target. The method used in this paper is a field study method in which the author directly observes the performance poses from KPP pratama pulogadung by doing question and answer and observation and method of study libraries Methods of data collection directed to search data and information by reading and studying books and regulations relating to this LPKL duty. The results of the discussion indicate that (1) Problem solving of taxpayer compliance in reporting tax return period of Article 23 can already be said to be very compliant (85% -100%) where in 2015 the level of compliance is 86.00% and year 2016 88.00% .Key Words: Income Tax Article 23, taxpayer, receipt